Effect of normobaric oxygen therapy on wound healing in patients with minor tissue loss from critical limb ischemia: A randomized clinical trial - P. Prasartritha (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2019. Objective: The present study is to evaluate the effect of normobaric oxygen therapy on wound healing in patients who presented with minor tissue loss from critical limb ischemia. Materials and Methods: This randomized controlled trial was conducted at Ramathibodi Hospital. From May 2017 to January 2018, critical limb ischemia patients with minor tissue loss were randomly assigned to be treated with or without normobaric oxygen therapy for four weeks. The primary outcome is to evaluate the wound healing by measuring the wound surface area. The secondary outcome is to evaluate the change in the transcutaneous oxygen tension at pre-and post-treatment and also complications from the treatment. Results: We assigned 28 patients with minor tissue loss into two groups (after excluding one patient from each group due to infection): 14 patients each group. The wound surface area at four-week times was smaller in intervention group (-0.06+1.25 cm2) but was larger in control group (0.825+1.10 cm2) without statistical significance (p = 0.057). Likewise, the transcutaneous oxygen tension in the intervention group showed superior result compared to the control group (3.22+9.54 vs.-3.02+7.25 mmHg) though there was no statistical significance (p = 0.059). Conclusion: Normobaric oxygen therapy may be beneficial for increasing wound healing in the critical limb ischemia patients who presented with minor tissue loss.